Nocturnal Melatonin Deficiency in Colorectal Cancer: Independent Predictive Value Beyond Sleep Quality
Background/Aim: Melatonin is a cytoprotective hormone with antioxidant activity and also mediates regulatory effects that inhibit tumor proliferation and angiogenesis. This study aimed to evaluate serum melatonin levels and sleep quality in patients with newly diagnosed colorectal cancer (CRC) compared with controls and to investigate whether melatonin could serve as a potential biomarker. Materials and Methods: A total of 71 participants (36 CRC, 35 controls) were included. Blood samples were obtained between 01:00- 02:00 am and serum melatonin was measured using a high-sensitivity (ELISA) Enzyme-Linked Immunosorbent Assay kit. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI) and sleep apnea risk was determined by the STOP-Bang questionnaire. Group comparisons were performed, followed by multivariable logistic regression and receiver-operating characteristic analysis. Results: Colorectal cancer patients had significantly lower nocturnal serum melatonin concentrations (131.1 Å